2017
DOI: 10.1002/2327-6924.12532
|View full text |Cite
|
Sign up to set email alerts
|

The pathophysiology, incidence, impact, and treatment of opioid‐induced nausea and vomiting

Abstract: Purpose Opioid medications are integral in managing acute moderate‐to‐severe pain. Opioid analgesics bind to μ (mu), κ (kappa), or δ (delta) opioid receptors in the brain, spinal cord, and digestive tract. However, opioids cause adverse effects that may interfere with their therapeutic use. Some adverse effects wane over time, but patients using opioids for acute pain struggle with opioid‐induced nausea and vomiting (OINV) the entire time they take the opioid. This article discusses the underlying mechanisms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 63 publications
2
31
1
2
Order By: Relevance
“…Therefore, we speculate that the signifcant difference in the incidence of nausea between the two groups may result from the different opioid with IV-PCA. Multiple factors may contribute to opioid induced nausea and vomiting, including activation of opioid receptors in the chemoreceptor trigger zone, vestibular apparatus, and gastrointestinal tract [ 36 ]. Coda BA et al found that there was no significant difference in nausea while compared hydromorphone, morphine and sufentanil IV-PCA in patients with oral mucositis pain following bone marrow transplantation [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we speculate that the signifcant difference in the incidence of nausea between the two groups may result from the different opioid with IV-PCA. Multiple factors may contribute to opioid induced nausea and vomiting, including activation of opioid receptors in the chemoreceptor trigger zone, vestibular apparatus, and gastrointestinal tract [ 36 ]. Coda BA et al found that there was no significant difference in nausea while compared hydromorphone, morphine and sufentanil IV-PCA in patients with oral mucositis pain following bone marrow transplantation [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The predominant adverse effect observed in this cohort was nausea, vomiting, that required antiemetic administration. In fact, about 40% of patients receiving opioids have been shown to experience nausea, and up to 25% may experience vomiting after opioid administration [ 23 , 24 ]. Patients rate nausea, vomiting after surgery worse than surgical pain [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Feldman, Lee, and Fiore (2015) claim that recovery tools should include aspects of importance for the patient. Nausea is a symptom that patients find unpleasant and also has an impact on the early physical recovery process (Allvin, Ehnfors, Rawal, & Idvall, 2008;Mallick-Searle & Fillman, 2017;Myles & Wengritzky, 2012). Regular monitoring for nausea is recommended to enable early treatment (Franck et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Programmes for enhanced recovery after surgery (ERAS) have been mentioned as a paradigm shift intended to support healthcare professionals in optimizing postoperative care (Fearon et al, 2005;Lombardi, Berend, & Adams, 2010). The aim is to accelerate physical recovery by minimizing complications such as infections, and reducing length of hospital stay (Fearon et al, 2005).…”
Section: Introductionmentioning
confidence: 99%